A preliminary study on the golden apple (Spondia dulcis): production and marketing in Grenada - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2020)
The document explains that the present effort is a proven product of how much could be acheived when inter-programme and inter-institutional cooperation is used towards the analysis of the commodity system of a crop with potential but with practically no records.